Deep Transitions: Towards a comprehensive framework for mapping major continuities and ruptures in industrial modernity. (January 2022) - Kanger, Laur; Tinits, Peeter; Pahker, Anna-Kati; Orru, Kati; Tiwari, Amaresh Kumar; Sillak, Silver; Šeļa, Artjoms; Vaik, Kristiina
Highlights: Provides a multi-dimensional and multi-domain measurement of industrial modernity. Combines text mining of newspapers with data from various databases. Finds evidence of major continuities in 3 countries (AU, GER, RUS) between 1900 and 2020. Detects rupture in environmental discourse and institutions but less so in practices. Changes in optimism about technological innovation are less visible in comparison. Abstract: The world is confronted by a socio-ecological emergency, requiring rapid and deep decarbonization of a broad range of socio-technical systems. A recent Deep Transitions framework argues that this fundamentally unsustainable trajectory has been generated by the co-evolutionary dynamics of multiple systems during the last 250 years. Altering this direction requires transformation in industrial modernity – a set of most fundamental ideas, institutions, and practices characterizing every industrial society to date. Although the proponents of the framework suggest that this shift has been unfolding since the 1960s, no attempts have been made to operationalize the concept of industrial modernity and to assess this claim. This paper develops a comprehensive multi-dimensional and multi-domain approach for the measurement of industrial modernity. As such it seeks to provide empirical evidence of long-term continuities and emerging ruptures in the dominant ideas, institutions, and practices of industrial societies along the domains of environment and technology. Using a methodologically novel approach where the text mining of newspapers is combined with data from various databases the paper provides results from three countries – Australia, Germany, Soviet Union/Russia – between 1900 and 2020. Despite considerable country-level differences the results show shifts in public environmental discourse from the 1960s, followed by institutional changes from the 1980s but with only a modest change in practices. We also observe some change in the direction of innovative activities and their regulation coupled with a resurgent optimism in technology-environment discourse. The findings tentatively suggest that industrial modernity might be in the process of hollowing out along ideational and institutional dimensions in the environmental domain but less so in the domain of technology and innovation.